Competing or Interactive Effect Between Perceived Response Efficacy of Governmental Social Distancing Behaviors and Personal Freedom on Social Distancing Behaviors in the Chinese Adult General Population in Hong Kong - Yanqiu Yu; Joseph Tak Fai Lau; Mason Man Chun Lau (International Journal of Health Policy and Management, 2022)
BackgroundUptake of social distancing behaviors may be determined by a combination of individual perceptions and social values. The study investigated (1) the associations between individual perception of perceived response efficacy and social distancing behaviors, (2) the association between social value of perceived freedom infringement and social distancing behaviors, and (3) whether perceived freedom infringement would moderate the association between perceived response efficacy and social distancing behaviors. MethodsA cross-sectional telephone survey interviewed 300 adults in the Hong Kong adult general population during April 21-28, 2020. The instruments of social distancing behaviors, perceived response efficacy, and perceived freedom infringement assessed the frequencies of practicing seven types of social distancing behaviors in the past week, perceived response efficacy of four types of governmental social distancing measures/instructions, and a 5-point Likert scale item on perceived infringement on personal freedom regarding a governmental social distancing measure of banning gatherings of >4 people in public areas. Linear regression adjusted for background factors was performed; the interaction term of perceived response efficacy × perceived freedom infringement was tested. ResultsAbout 40.4%-83.0% of the respondents practiced various types of social distancing behaviors; 57.3%-75.0% perceived response efficacies of related governmental measures; about 20% showed perceived freedom infringement. Perceived response efficacy, but not perceived freedom infringement, was independently and positively associated with social distancing behaviors. Perceived freedom infringement significantly moderated the association between perceived response efficacy and social distancing behaviors; such a positive association was significant at higher (those scored “extremely agree”), but not lower (those scored “extremely disagree), levels of perceived freedom infringement. ConclusionPerceived response efficacy is a potential determinant of social distancing. However, the strength of such an association may be modified by opposing social values about personal freedom. Future studies are warranted to verify above findings and explore other potential determinants.